2021
DOI: 10.1097/qad.0000000000002719
|View full text |Cite
|
Sign up to set email alerts
|

Risk of birth defects and perinatal outcomes in HIV-infected women exposed to integrase strand inhibitors during pregnancy

Abstract: Objectives. Following an alert on neural tube defects and dolutegravir, we sought to evaluate if the exposure integrase strand transfer inhibitors (INSTIs) at conception was associated with birth defects or other adverse pregnancy outcomes. Methods :In the prospective national French Perinatal Cohort (EPF), we studied birth defects and other perinatal outcomes by matching each pregnant woman exposed to INSTIs with a pregnant woman exposed to darunavir/ritonavir receiving the same backbone of nucleoside reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“… 19 This early signal prompted concern regarding the safety of DTG use during pregnancy, and led the World Health Organization to temporarily suspend recommendation of DTG in this population. Reassuring follow-up findings from the Tsepamo study and others demonstrated lower rates of NTDs, though in some cases still higher than rates in populations exposed to non-DTG based ART; 20 , 21 , 22 , 23 however as DTG use continues to rise among pregnant women, and women of childbearing age living with HIV, it remains critical to better understand the implications of in utero DTG exposure on fetal development. Recent reports have identified potential interactions between DTG and folate uptake pathways, though the implications of these findings remain unclear, and findings in in vivo models are limited.…”
Section: Introductionmentioning
confidence: 97%
“… 19 This early signal prompted concern regarding the safety of DTG use during pregnancy, and led the World Health Organization to temporarily suspend recommendation of DTG in this population. Reassuring follow-up findings from the Tsepamo study and others demonstrated lower rates of NTDs, though in some cases still higher than rates in populations exposed to non-DTG based ART; 20 , 21 , 22 , 23 however as DTG use continues to rise among pregnant women, and women of childbearing age living with HIV, it remains critical to better understand the implications of in utero DTG exposure on fetal development. Recent reports have identified potential interactions between DTG and folate uptake pathways, though the implications of these findings remain unclear, and findings in in vivo models are limited.…”
Section: Introductionmentioning
confidence: 97%
“…The copyright holder for this preprint this version posted October 13, 2022. ; https://doi.org/10.1101/2022.10.10.22280923 doi: medRxiv preprint exposed to INSTI in the first trimester. [10,15] Ideally, the potential associations we identified should be confirmed in additional studies with larger sample sizes. We did not find significant associations between congenital anomalies and the use of INSTI in the second or third trimester.…”
Section: Discussionmentioning
confidence: 87%
“…It is important to note that the grain food supply in Botswana is not folate‐fortified, which may possibly contribute to insufficient folate levels in pregnant women, leading to an increased incidence of NTDs 26 . Since these initial reports, several clinical studies have failed to identify a significant association between dolutegravir exposure and NTDs 27‐29 . Additionally, data from in vivo studies examining any possible developmental toxicities associated with dolutegravir exposure have also been inconsistent 30‐32 .…”
Section: Folate Transport Pathwaysmentioning
confidence: 99%
“…26 Since these initial reports, several clinical studies have failed to identify a significant association between dolutegravir exposure and NTDs. [27][28][29] Additionally, data from in vivo studies examining any possible developmental toxicities associated with dolutegravir exposure have also been inconsistent. [30][31][32] Cabrera et al demonstrated that early exposure to dolutegravir in zebrafish resulted in developmental toxicities, with folic acid supplementation rescuing these defects.…”
Section: Folate Transport Pathwaysmentioning
confidence: 99%